Statyka Gęstych Regularnych Pasm Kratowych - Bojda, K.H.; Słomka, A. (Engineering Transactions, 1973)
In the paper are discussed the solutions of differential equations for uniform lattice-type truss strips, particular attention being paid to such systems which are simply supported along certain intermediate lines parallel to the edges of the strips. The solution is found by means of the Mikusinski operators.